First example of organocatalysis by cathodic N-heterocyclic carbene generation and accumulation using a divided electrochemical flow cell - Daniele Rocco; Ana A. Folgueiras-Amador; Richard C. D. Brown; Marta Feroci (Beilstein Journal of Organic Chemistry, 2022)
In this paper we present the first electrochemical generation of NHC carried out in a divided flow cell. The flow cell operated in the recycle mode. The need for a divided cell derived from the anodic electroactivity of the electrogenerated carbene. In order to have NHC accumulation in the catholyte, the Nafion membrane (cell separator) was pretreated with an alkaline solution. The formation of NHC was quantified as its reaction product with elemental sulfur. The NHC was successfully used as organocatalyst in two classical umpolung reactions of cinnamaldehyde: its cyclodimerization and its oxidative esterification.